EFEKTIVITAS LKPD LARUTAN PENYANGGA BERBASIS GUIDED INQUIRY LEARNING TERINTEGRASI ETNOSAINS UNTUK MENINGKATKAN KEMAMPUAN LITERASI KIMIA PESERTA DIDIK FASE F SMA - Kurniawan, Rahmi; Andromeda, Andromeda (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2025)
The Buffer Solution Student Worksheet (LKPD), developed using the Guided Inquiry Learning model and incorporating ethnoscience elements, has been validated by experts and rated as highly practical. However, its effectiveness in enhancing student outcomes had not been previously evaluated. This research aims to evaluate the effectiveness of the ethnoscience-integrated LKPD in enhancing students’ chemical literacy, specifically in the domains of context, content knowledge, and competence. A quasi-experimental approach was employed, using a non-equivalent control group design. The participants were 11th-grade students (Phase F) from UNP Laboratory Development Senior High School. Two classes were selected through purposive, homogenous sampling: XI F4 as the experimental group and XI F6 as the control group. The instrument used was a 15-question multiple-choice test measuring chemical literacy, which was validated for reliability, difficulty, and discrimination index. Findings revealed that the experimental group achieved an average N-Gain score of 0.628, categorized as moderately effective, while the control group scored 0.495, indicating lower effectiveness. An independent samples t-test conducted at a ? = 0,05 significance level showed tcount (3,649) > ttable (1,672), leading to the rejection of the H0 hypothesis. Consequently, the results suggest that the ethnoscience-based guided inquiry LKPD effectively improves students’ chemical literacy. ABSTRAKLembar Kerja Peserta Didik (LKPD) larutan penyangga berbasis Guided Inquiry Learning terintegrasi etnosains telah dinyatakan valid dan sangat praktis berdasarkan hasil uji ahli, namun belum teruji efektivitasnya. Penelitian ini bertujuan untuk mengkaji efektivitas LKPD larutan penyangga berbasis guided inquiry learning terintegrasi etnosains untuk meningkatkan kemampuan literasi kimia peserta didik aspek konteks, pengetahuan dan kompetensi. Penelitian ini menggunakan metode quasi-experimental, desain non-equivalent control group design. Populasi penelitian adalah peserta didik kelas XI Fase F SMA Pembangunan Laboratorium UNP. Sampel terdiri dari kelas XI F4 (eksperimen) dan XI F6 (kontrol) yang  ditentukan dengan teknik purposive, homogenous sampling. Data didapatkan melalui tes pilihan ganda literasi kimia sebanyak 15 soal yang telah diuji validitas, reliabilitas, daya pembeda, dan tingkat kesukarannya. Hasil analisis menunjukkan rata-rata skor N-Gain literasi kimia kelas eksperimen 0,628 (cukup efektif), sedangkan kelas kontrol 0,495 (kurang efektif). Perbedaan ini diperkuat melalui uji (t) sebagai uji hipotesis dengan taraf signifikansi ? = 0,05, menunjukkan bahwa thitung (3,649) > ttabel (1,672) sehingga H0 ditolak dan H1 diterima. Dengan demikian, kemampuan literasi kimia peserta didik di kelas eksperimen lebih tinggi dibandingkan  kelas kontrol, sehingga LKPD larutan penyangga berbasis Guided Inquiry Learning terintegrasi etnosains efektif untuk meningkatkan kemampuan literasi kimia peserta didik.